Supporting the UN's Sustainable Development Goals: reconceptualising a 'sustainable development assessment tool' for the health and care system in England. (March 2019) - Hewitt, Michael; Molthan-Hill, Petra; Lomax, Richard; Baddley, Jerome
Aim: As one of the biggest organisations in the world, the National Health Service (NHS) in England can contribute considerably to the United Nations' Sustainable Development Goals (UN's SDGs). In order to optimise this, this study evaluated and reconceptualised a sustainable development assessment tool for health and care settings in England. Methods: A quantitative survey and user/expert discussion panels were conducted to evaluate and reconceptualise the existing sustainable development assessment tool used by the NHS in England, the so-called 'Good Corporate Citizenship Assessment Tool', including potential improvements such as the integration of the UN's SDGs. Results: A reconceptualised self-assessment tool integrating the UN's SDGs was developed and implemented online as the 'Sustainable Development Assessment Tool' (SDAT). Further improvements included a process-oriented redesign and the creation of new modules and cross-sections aligning them with the leads responsible for the implementation of key initiatives in NHS organisations, which would contribute to achieving the targets of the SDGs. Conclusion: User/expert involvement has enabled an informed approach to a reconceptualisation of a sustainable assessment tool for health and care settings. The tool will support organisations to build their mandatory Sustainable Development Management Plans, as part of the National Public Health Outcomes Framework. Alignment of the tool to the UN's SDGs provides an opportunity for health and care organisations to demonstrate accountability and progress against the UN's set of transformational goals. Furthermore, the tool could be adapted to other public service providers.